Perpanjangan Aliansi Keamanan Jepang-Amerika Serikat Pada Tahun 2013 (Perspektif Jepang) - Elli Listiana ; Erna Kurniawati (Jurnal Paradigma, 2015)
Japan-United States engaged in alliance security since 1951. In 2013 both countries declared to continue and extend the alliance. This paper analyzes the Japanese interest in theextension ofalliance security agreement with United States. Japan-United States made a commitment to continue and extend the security alliance on October 3, 2014 in Tokyo. During the meeting,bothcountries agreedtocontinue,strengthenthe security alliance,and build a balanced and effective alliance in order to increase the responsibility and contribution of international peace and security. In addition, the United States also declared a commitment togive security protection for Japan to respond the dynamics of security in East Asia. The new agreements of the security alliance resulted coincide with the meeting of the Security Consultative Committee (SCC) 2013. SCC 2013 resulted agreements and new security cooperation that has never been done before.The extension ofthe security alliance is very bene cial for Japan. The new alliance showed consistency of United States to give security assistance to Japan to face the security dynamics in East Asia. In addition, the alliance will provide an opportunity forJapan to make more pro active contribution to international peace and security.